315 Athlete Sleep and Mental Health: Differences by Gender, Race, and Ethnicity. (3rd May 2021) - Huskey, Alisa; Kim, Kelly; Emert, Sarah; Auerbach, Alex; Webb, Rachel; Skog, Michelle; Grandner, Michael; Taylor, Daniel
Abstract: Introduction: Sleep is important for athletic and academic performance, injury risk and recovery, and physical and mental health. However, athletes commonly have poor and insufficient sleep, which may be worsened by their inflexible schedules, stress, traveling, and timing of competition. To date, little is known about the relationship between sleep problems and risk for mental health problems in college student athletes. Almost nothing is known about gender, racial and ethnic sleep disparities in this group. The current study aimed to examine the cross-sectional relationships between sleep disorder symptoms and mental health symptoms, further examining differences by gender, race, and ethnicity. Methods: Student athletes (N = 1033) from four universities within the Pacific Athletic Conference (PAC-12) were surveyed using previously-validated mental health questionnaires. Since few individuals self-identified as Asian, American Indian/Alaskan Native, Native Hawaiian/Pacific Islander, or "Other, " the race variable was recoded into three groups: White, Black, and Other Underrepresented groups. Gender, race, and ethnicity differences on Athlete Sleep Screening Questionnaire (ASSQ) total scores were examined using a three separate MANOVAs. Next, sleep-disorder symptoms were classified as clinically relevant (n=174) or not (n=733) based on established cutoff values on the ASSQ. Gender and sleep disorder differences on mental health total scores were examined using a MANOVA. Results: Women athletes reported significantly worse sleep disorder symptoms as a whole. In addition, Black athletes had worse sleep disorder symptoms. There was a trend for women with sleep problems to have higher PC-PTSD scores than women without sleep problems. In addition, athletes in the Other Underrepresented race group with sleep problems also had greater depression, PTSD, and psychotic symptom severity than White or Black student athletes. There was also a trend for Hispanic athletes with sleep disorder symptoms to have greater ADHD symptom severity. Conclusion: To further examine individual differences in specific components of sleep symptoms, sleep duration, insomnia symptoms, medication, quality will be reported in the poster presentation. Future studies are needed to understand whether frequency and chronicity of athletic and external stressors, explain elevations in sleep and other psychiatrics symptoms in student athletes. Support (if any): This project was funded by a PAC-12, Mental Health Coordinating Unit Grant.